Strategies to Minimize Bullying and Enhance Motivation in English Language Learning: A Literature Review - Rochma, Anis Firdatul (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2024)
Maintaining strong motivation, self-esteem, and self-confidence is crucial for learners to achieve proficiency in English. However, traditional and cyberbullying are significant issues that can undermine learners' motivation, leading to a decline in English learning progress. Henceforth, the present study is projected to investigate the impacts of bullying toward the learners’ motivation in learning English. The qualitative research is adopted by specifying a detailed description of both traditional and cyberbullying carried out in English language learning. The discussion related to why the act of bullying might happen in English language learning is also presented. The analysis reveals that experiences of bullying significantly affect EFL learners' intrinsic and extrinsic motivation. The study suggests that incorporating educational philosophy can offer effective strategies to reduce bullying and foster greater motivation in English learning environments.